Social media usage and academic performance of library and information science undergraduates in universities in Edo and Delta State, Nigeria - Ogbomo, Monday Obaidjevwe; Ivwighreghweta, Oghenetega (Qualitative and Quantitative Methods in Libraries; Vol 7 No 3 (2018): September 2018 Issue, 2019)
Since the last few decades, technology has grown immensely and has brought major changes globally. This study investigated social media usage and academic performance of library and information science undergraduates in universities in Edo and Delta State, Nigeria. Four research questions were answered and one hypothesis tested. The descriptive survey design was employed for this study. The population of the study is 1524. The sample size for this study is 500. The questionnaire was the instrument used for data collection. Data were analyzed using frequency, statistical mean and z-test statistics. Findings from this study revealed that the undergraduates indicated overwhelmingly that they use social media sites. The reasons for their usage of social media sites are for academic work and research purpose. It was found that they invest 1-60 minutes on social media sites in a day. It was further revealed that they visit Facebook sites, Youtube, Google+, Wikipedia and Whatsapp. The study revealed that the undergraduates are within the CGPA of 3.50-4.49 indicating a high academic performance. The study further showed that there is no significant relationship between the amount of hours invested on social media sites and academic performance of the students. Implying that an increase in the amount of hours invested on use of social media sites may not lead to a corresponding increase in academic performance of the LIS undergraduates in the respective universities.